Lord John and the hand of devils - Gabaldon, Diana (New York : Delta Trade Paperbacks, 2008)
A collection of three novellas by Diana Gabaldon that feature Lord John Grey, an eighteenth-century English soldier whose homosexual lifestyle often lands him in unusual, and dangerous, situations.
Lord John and the hellfire club -- Lord John and the succubus -- Lord John and the haunted soldier.
"The Lord John Grey series"--Prelim p.
Kirkus Review
Publisher's Weekly
Adult.
Adult
Keywords: Nobility -- England -- Fiction; Seven Years' War, 1756-1763 -- Fiction; Historical fiction; Nobility -- England -- Fiction; Seven Years' War, 1756-1763 -- Fiction; Historical fiction